The long-term earnings' effects of a credit market disruption - Effrosyni Adamopoulou; Marta De Philippis; Enrico Sette; Eliana Viviano (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
This paper studies the long-term consequences on firms and workers of the credit crunch triggered by the 2007-2008 global financial crisis. Relying on a unique matched bank-employer-employee administrative dataset, we construct a firm-specific credit supply shock and examine firms' and workers' outcomes for 11 years after the crisis. We find that highly-exposed firms shrink permanently and invest less; these effects are larger for high capital-intensive firms. The impact on workers' earnings is also long-lasting, especially for high skilled workers, who are more complementary to capital. Displaced workers reallocate mostly to low capital-intensive firms, experiencing persistent wage losses.
Keywords: E24; E44; G21; J21; J31; J63; 330; credit crunch; employment; wages; long term effects; linked bank-employer-employee panel data; capital-skill complementarity